Compressive behaviour of a tire recycled steel and textil fiber concrete subjected to fire - Santos, C.C. (2015)
The use of rubber aggregates, steel and textile fibres recycled from tires in concrete is a solution that it is being studied by several authors around the world. A few works have been carried out at room temperature but very scarce at high temperatures. This paper presents the results of a research with the aim to evaluate the behaviour at high temperatures of a concrete made with different amounts of recycled textile and steel fibres from tires. The study considered five concrete compositions, with the same water/cement ratio (W/C=0.43), differing only in the type and quantity of fibers incorporated in the mixture. Thus, a reference composition (0% fiber), two compositions with 30 and 70kg/m3 of steel fibers and a composition with 2 and 4kg/m3 of textile fibers from tires were tested. The concrete was tested for a load level of 0.5fcd and different maximum temperature levels (20, 300, 500 and 700ºC).